2006
DOI: 10.1029/2005ja011346
|View full text |Cite
|
Sign up to set email alerts
|

Perturbations of midlatitude subionospheric VLF signals associated with lower ionospheric disturbances during major geomagnetic storms

Abstract: We examine the effects on the midlatitude ionospheric D region of the 7 April 2000 storm and the “Halloween storm” of late October 2003 by means of the associated perturbations of several subionospheric VLF signals propagating in both the northern and southern hemispheres. We use VLF nighttime data from the Holographic Array for Ionospheric/Lightning Research (HAIL), located in the United States (L = 2–3), as well as data from Palmer Station, Antarctica (L = 2.4). On 7 April 2000, a ∼5 dB depression in VLF amp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
53
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(56 citation statements)
references
References 32 publications
3
53
0
Order By: Relevance
“…The diurnal plots for both NWC and NPM signals were closely inspected for the period 12 to 18 December 2006. No apparent increase in signal fluctuations were noticed during day or nighttime as reported by previous researchers such as Peter et al (2006) who reported amplitude fluctuations in the nighttime data and Belrose and Thomas (1968) who reported fluctuations in the phase during twilight and nighttime during the geomagnetic storms in the mid-latitude regions. The relevant phase data which were intercepted by short-term switching off of transmitters have not been used for analysis, since phase does not follow the same value as before the transmitter was switched off.…”
Section: Geomagnetic Storm Associated Vlf Perturbationssupporting
confidence: 61%
See 1 more Smart Citation
“…The diurnal plots for both NWC and NPM signals were closely inspected for the period 12 to 18 December 2006. No apparent increase in signal fluctuations were noticed during day or nighttime as reported by previous researchers such as Peter et al (2006) who reported amplitude fluctuations in the nighttime data and Belrose and Thomas (1968) who reported fluctuations in the phase during twilight and nighttime during the geomagnetic storms in the mid-latitude regions. The relevant phase data which were intercepted by short-term switching off of transmitters have not been used for analysis, since phase does not follow the same value as before the transmitter was switched off.…”
Section: Geomagnetic Storm Associated Vlf Perturbationssupporting
confidence: 61%
“…They obtained negative phase and amplitude variations of the VLF signal both during day and nighttimes during the main storm phase days, but the nighttime variations were more pronounced. There have not been other studies on magnetic storm associated subionospheric changes purely at low latitude paths; however, there have been several studies on VLF perturbations due to storm-induced energetic electron precipitation at mid and high latitudes (e.g., Peter et al 2006;Clilverd et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The paper of Peter et al (2006) demonstrates that subionospheric VLF signals can be used as a diagnostic of high-energy auroral precipitation at midlatitudes during disturbed geomagnetic conditions. The onset of fluctuations in the VLF amplitude data occurred immediately after the depression of the signal amplitude.…”
Section: 68mentioning
confidence: 99%
“…In fact, they reported that VLF events occurred in higher number during recovery phase of geomagnetic storms. Peter et al (2006) examined the effects of two geomagnetic storms on the midlatitude D-region using several VLF signal paths in both the northern and southern hemispheres. The amplitude and phase of the VLF signals exhibited perturbations with increased geomagnetic activity and with fluctuations in amplitude persisting several hours after the occurrence of the geomagnetic storm.…”
Section: 68mentioning
confidence: 99%
“…The enhancement in the VLF amplitude was most likely due to additional ionization (basically increase in electron concentration) produced by this earthquake in the lower ionosphere. We have looked for four possible mechanisms for electron density enhancement in the D region and hence the enhancement in JJI VLF amplitude: solar flares (Zigman et al, 2007), geomagnetic storm (Peter et al, 2006), lower ionospheric heating due to lightning discharges causing early/fast VLF events (Inan et al, 1996), and seismic origin due to 12 May 2008 EQ. We have examined details of all possible events; solar flare events are of few minute duration whose effect can be easily identified in the VLF amplitude data.…”
Section: Amplitude Perturbationsmentioning
confidence: 99%